Proton and Helium-4 Ion Beams for Hadron Therapy: Depth, Lateral, and Secondary Particle Dose Calculations - O. Allaoui; A. Didi; E. M. Alibrahmi; E. M. Chakir; Z. Sadoune (National Research and Innovation Agency, 2026)
This study compares Monte Carlo simulations of dose distributions from proton and helium-4 ion beams in an aqueous medium using the MCNP code. Proton beams (60-240 MeV) and helium-4 beams (80-240 MeV, 520 MeV) are evaluated for their ballistic properties in hadron therapy, including penetration depth, lateral dose spread, and secondary particle production. Helium-4 ions, with higher mass and charge, exhibit sharper Bragg peaks and less lateral scattering than protons, suggesting better dose conformity. They also produce fewer long-range secondary particles, potentially reducing unintended dose to healthy tissues. These results highlight the potential of helium-4 ions as a viable alternative to proton therapy for more precise dose control and reduced collateral damage.